Taxonomic note of Oberea fuscipennis (Chevrolat, 1852) based on morphological and DNA barcode data (Coleoptera, Cerambycidae, Lamiinae) - Li, Zhu; Tian, Lichao; Cuccodoro, Giulio; Chen, Li; Lu, Cheng (Zootaxa, 2016)
Oberea fuscipennis (Chevrolat, 1852) species group is revised based on morphology and DNA barcode data. Oberea diversipes Pic, 1919 and O. infratestacea Pic, 1936 are restored from synonymy. The following two new synonymies are proposed: Oberea fuscipennis ssp. fairmairei Breuning, 1962 = Oberea diversipes Pic, 1919; and Oberea hanoiensis Pic, 1923 = O. fuscipennis (Chevrolat, 1852)